Efektivitas Modifikasi Perilaku untuk Meningkatkan Keterampilan Komunikasi Anak dengan Gangguan Bahasa - Mira Riani (Fakultas Psikologi Universitas Tarumanagara, 2021)
Expressive language disorder is difficulty using words to communicate desires and ideas. This study aims to intervene to improve communication skills in children with expressive language disorders using behavior modification. This study uses a qualitative method with a case study approach to see changes in behavior that occur to the subject. The research subject was male, 4 years 8 months old. Researchers use several techniques in behavior modification such as token economy, imitation, and modeling. The intervention was carried out in 7 sessions, each session taking 30 minutes to 1 hour. The intervention was carried out for seven weeks. The results of the intervention indicated an improvement in the subject's language and communication. The subject is quite capable of pronouncing several vocabulary words clearly and precisely. There are new vocabulary additions that are not familiar with the subject. The subject mentions the words without eliminating the prefix or ending of the word and the subject has been able to compose 2 to 3 simple words in 1 sentence. Based on the intervention that has been given to the subject, it can be concluded that the provision of behavior modification therapy by combining token economy, imitation and modeling techniques is quite effective in improving the subject's communication skills. The subject shows a change in the ability to communicate.